Decline in mortality, AIDS, and hospital admissions in perinatally HIV-1 infected children in the United Kingdom and Ireland. Issue 7422 (30th October 2003) - Gibb, D M; Duong, T; Tookey, P A; Sharland, M; Tudor-Williams, G; Novelli, V; Butler, K; Riordan, A; Farrelly, L; Masters, J; Peckham, C S; Dunn, D T
Abstract: Objective To describe changes in demographic factors, disease progression, hospital admissions, and use of antiretroviral therapy in children with HIV. Design Active surveillance through the national study of HIV in pregnancy and childhood (NSHPC) and additional data from a subset of children in the collaborative HIV paediatric study (CHIPS). Setting United Kingdom and Ireland. Participants 944 children with perinatally acquired HIV-1 under clinical care. Main outcome measures Changes over time in progression to AIDS and death, hospital admission rates, and use of antiretroviral therapy. Results 944 children with perinatally acquired HIV were reported in the United Kingdom and Ireland by October 2002; 628 (67%) were black African, 205 (22%) were aged ≥ 10 years at last follow up, 193 (20%) are known to have died. The proportion of children presenting who were born abroad increased from 20% in 1994-5 to 60% during 2000-2. Mortality was stable before 1997 at 9.3 per 100 child years at risk but fell to 2.0 in 2001-2 (trend P < 0.001). Progression to AIDS also declined (P < 0.001). From 1997 onwards the proportion of children on three or four drug antiretroviral therapy increased. Hospital admission rates declined by 80%, but with more children in follow up the absolute number of admissions fell by only 26%. Conclusion In children with HIV infection, mortality, AIDS, and hospital admission rates have declined substantially since the introduction of three or four drug antiretroviral therapy in 1997. As infected children in the United Kingdom and Ireland are living longer, there is an increasing need to address their medical, social, and psychological needs as they enter adolescence and adult life.